Fungitoxicity Against Botrytis Cinerea of a Flavonoid Isolated from Pseudognaphalium Robustum - Cotoras-Tadic, M; Aguirre-Quintana, M; Aguirre-Quintana, M; Mendoza-Espinola, L; Mendoza-Espinola, L; Castro-Valenzuela, P; Castro-Valenzuela, P (2011)
Sin Editorial Disponible